Colorimetric methods using synthetic and alternative reagents for pollen viability of Bixa orellana L. (Research, Society and Development, 2020)
The study of pollen viability is essential for genetic improvement, as it shows the fertility of species. Thus, estimates of pollen grains of B. orellana L., in viable and non-viable, are necessary in order to search for efficient, safe and preferably, accessible and easy-to-manipulate dyes to distinguish the reproductive potential of male gametes in the annatto. The objective was to evaluate the potential of five colorimetric tests, three synthetic and two alternative reagents, in order to estimate the pollen viability of B. orellana L. A mix of 50 flower buds in the pre-anthesis stage was collected in different locations, in the municipality of Alta Floresta - MT. In the laboratory, the pollen grains were tested with three synthetic dyes: Alexander reagent, 2% Lugol and Roeser method (Astra blue + Fuchsin); Two more natural, extracted from the red poppy flower (Hibisco sp.) And from the Jatobá bark (Hymenaea courbaril L.). Pollen viability was estimated by the percentage of viable and non-viable pollen grains. A completely randomized design was used, consisting of 5 treatments and 10 repetitions. The data were submitted to the Tukey test at 5% probability. The synthetic dyes Reagent de alexander and Lugol 2% obtained the highest averages, however, they did not differ by the average test of the alternative dye of Hibisco sp. which proved to be suitable and recommended for use in cytogenetics due to its low cost, ease of acquisition and handling, making it a strategic alternative when compared to conventional synthetic dyes.